Effects of Strobzlanthes Crispus Crude and Tea Extracts in Streptozotocin-Induced Hyperglycemic Rats - Abu Bakar, Mohd Fadzelly (2006)
Strobilanthes crispus leaf has been used ethnomedically to treat diabetes mellitus and related disorders in Asia. The first part of this study is to develop a tea from leaves of S. crisps and investigate its antioxidant properties in vitro. Fermented and unfermented teas from young and old leaves of S. crispus were developed according to Camellia sinensis and Camellia theifera preparations for black and green tea, respectively. Three methods were used to determine the antioxidant activities i.e 1) p-carotene bleaching method 2) DPPH fiee radical scavenging assay 3) Ferric reducinglantioxidant power (FRAP) assay. The total phenolic content was also estimated using Folin-Ciocalteu method. The result showed that unfermented S. crisps tea displayed a higher antioxidant activity compared to fermented S. crispus tea. Tea developed from old or matured leaves possessed higher antioxidant activity compared to young leaves. However, commercial green (Sencha, UK) and black (Boh, Malaysia) tea that were developed from leaves of C. sinensis exhibited higher antioxidant activity among all teas tested. The second part of this study was aimed at determining the effect of S. crispus crude extract on STZ-induced hyperglycemic rats. S. crispus (young and old leaves) were extracted with distilled water and given to normal and hyperglycernic rats at concentrations of 2.5, 5.0 and 7.5% for 21 days. Plasma glucose, lipid profile (total cholesterol, triglyceride, HDL-cholesterol, LDL-cholesterol), total antioxidant status and serum potassium and magnesium contents were determined on baseline (day O), day 7 and day 21. The results showed that S. crispus crude extract at concentrations of 2.5, 5.0 and 7.5% from old or matured leaves reduced glucose level significantly in hyperglycemic rats (~4.05). Third part of this study evaluated the effect of S. crispus fermented and unfermented tea in STZ-induced hyperglycemic rats at a concentration of 2% for 21 days. Plasma glucose, lipid profile (total cholesterol, triglyceride, HDLcholesterol, LDL-cholesterol), total antioxidant status and serum potassium and magnesium contents were determined during baseline (day O), day 7 and day 21. The results showed that both fermented and unfermented S. crispus tea reduced glucose level in hyperglycemic rats (p<0.05). Fermented and unfermented S. crispus tea also improved antioxidant status and lipid profile in hyperglycemic rats by lowering the total cholesterol, triglyceride, and LDL-cholesterol. Total antioxidant status and HDLcholesterol also increased in hyperglycemic rats treated with fermented or unfermented tea S. crispus. Both fermented or unfermented S. crisps tea failed to prevent the reduction of serum magnesium in hyperglycemic rats.